Vertical and horizontal surface displacements near Jakobshavn Isbrae driven by melt-induced and dynamic ice loss - Karina Nielsen; Shfaqat A. Khan; SPADA, GIORGIO; John Wahr; Michael Bevis; Lin Liu; Tonie van Dam (Journal of Geophysical Research: Solid Earth, 2013)
[1] We analyze Global Positioning System (GPS) time series of relative vertical and horizontal surface displacements from 2006 to 2012 at four GPS sites located between ∼5 and ∼150 km from the front of Jakobshavn Isbræ (JI) in west Greenland. Horizontal displacements during 2006–2010 at KAGA, ILUL, and QEQE, relative to the site AASI, are directed toward north-west, suggesting that the main mass loss signal is located near the frontal portion of JI. The directions of the observed displacements are supported by modeled displacements, derived from NASA's Airborne Topographic Mapper (ATM) surveys of surface elevations from 2006, 2009, and 2010. However, horizontal displacements during 2010–2012 at KAGA and ILUL are directed more towards the west suggesting a change in the spatial distribution of the ice mass loss. In addition, we observe an increase in the uplift rate during 2010–2012 as compared to 2006–2010. The sudden change in vertical and horizontal displacements is due to enhanced melt-induced ice loss in 2010 and 2012.